2020
DOI: 10.3389/fphar.2020.01331
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Neurologic Benefit of Levosimendan vs Dobutamine in Patients With Low Cardiac Output Syndrome After Cardiac Surgery: Clinical Trial FIM-BGC-2014-01

Abstract: Question: Do levosimendan and dobutamine for the treatment of LCOS have different neurological and renal effects? Finding: Significant variations were observed in the levosimendan group in relation to AKI stage after 24 and 48 h but not in cardiac index or renal blood flow. Meaning: The beneficial effects of Levosimendan could be mediated by a postconditioning effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The outcome of our study revealed ESRD with regular hemodialysis occurred in 2% of the patients, however, Lannemyr, et al reported that levosimendan increases glomerular filtration rate and thus may be the preferred inotropic agent for treating patients with the cardiorenal syndrome (11) which is comparable with Guerrero-Orriach, et al who found that levels of creatinine decreased in the levosimendan treated patients, showing significant variations at 24 and 48 h after treatment (12). Our study showed that there were no statistically significant differences between studied groups in myocardial infarction.…”
Section: Discussionsupporting
confidence: 67%
“…The outcome of our study revealed ESRD with regular hemodialysis occurred in 2% of the patients, however, Lannemyr, et al reported that levosimendan increases glomerular filtration rate and thus may be the preferred inotropic agent for treating patients with the cardiorenal syndrome (11) which is comparable with Guerrero-Orriach, et al who found that levels of creatinine decreased in the levosimendan treated patients, showing significant variations at 24 and 48 h after treatment (12). Our study showed that there were no statistically significant differences between studied groups in myocardial infarction.…”
Section: Discussionsupporting
confidence: 67%
“…The same research group [ 80 ] has also conducted a more conventionally configured RCT in 60 patients with confirmed LCOS after cardiac surgery, comparing the impact on kidney failure of levosimendan (0.1 μg/kg/min for 24 h) or dobutamine (starting infusion rate 5 μg/kg/min, thereafter variable according to response). Renal status was assessed using the acute kidney injury scale (AKIS).…”
Section: In the Presence Of Renal Dysfunction/failurementioning
confidence: 99%
“…Due to its calcium-sensing properties, levosimendan may be more beneficial in relaxing the myocardium compared to catecholamines during diastole [22]. Levosimendan can effectively protect liver and kidney functions while preserving heart function, regardless of the presence of hepatic or renal impairment before it is used [23][24][25][26][27][28]. Partly of these protective effects due to their antiinflammatory and anti-apoptotic properties [29,30].…”
Section: Discussionmentioning
confidence: 99%